(untitled) (Asian Journal of Medical and Biological Research, 2024)
Global antibiotic resistance is a pressing issue, especially in Bangladesh, due to its widespread use, poor surveillance, and high treatment costs. This study compared antibiotic use between Rohingya and rural Bangladeshi residents, aiming to predict the frequency and tendency of commonly used antibiotics across different community levels. This was a cross-sectional descriptive study using a questionnaire. It involved Cox’s Bazar camp, Tangail, and Bogura rural areas. Most participants were male, with 46.8% graduates and 20.8% untrained from mixed economic backgrounds. The study revealed that 62% adhered to doctors’ orders, 28.5% followed pharmacists’ recommendations, 6% sourced antibiotics from various places, 3% self-medicated, and 1% relied on advice from friends or relatives. Alarmingly, 25.3% did not complete their antibiotic courses. Age, region, advisor status, and education level were correlated with antibiotic use (P<0.05), whereas socioeconomic status was not. The most commonly used medications among both rural and FDMN populations were azithromycin, ciprofloxacin, amoxicillin, and metronidazole. These findings highlight gaps in antibiotic use and adherence, with many not completing their treatments. Despite educational and economic variations, there is a general lack of concern about AMR, emphasizing the need for better awareness of and adherence to guidelines. Asian J. Med. Biol. Res. 2024, 10(3), 122-130